New look at the role of progerin in skin aging - Skoczyńska, Anna; Budzisz, Elżbieta; Dana, Agnieszka; Rotsztejn, Helena (Menopause Review/Przegląd Menopauzalny, 2015)
Current literature data indicate that progerin, which is a mutant of lamin A, may be one of several previously known physiological biomarkers of the aging process which begins at the age of 30. Lamins belong to the family of intermediate filaments type V and are an important component of the nuclear envelope (NE). The physiological processes of an alternative splicing of LMNA (lamin A/C) gene and posttranslational processing result in the formation of different variants of this gene. Prelamin A is generated in cytosol and modified by respective enzymes. In the final step, 15-aa peptide is released at the C-terminus, resulting in mature lamin A. Point mutation of cytosine to thymine at position 1824 in exon 11 of LMNA gene causes a truncated form of lamin A, which is defined as progerin. In the course of time, progerin is mainly found in skin fibroblasts and reticular layers of terminally differentiated keratinocytes. Changes take place in the nucleus and they are similar to those observed in patients with Hutchinson-Gilford progeria syndrome and refer mainly to an increase in the amount of reactive oxygen species which reduce the level of antioxidant enzymes, DNA damage and histone modification. There are still pending studies on working out new anti-aging strategies and the skin is the main area of research. Biomimetic peptides (analogues of elafin) are used in cosmetics to reduce the formation of progerin.